2012
DOI: 10.1002/cncr.27653
|View full text |Cite
|
Sign up to set email alerts
|

Identification of polymorphisms in ultraconserved elements associated with clinical outcomes in locally advanced colorectal adenocarcinoma

Abstract: Background Ultraconserved elements (UCEs) are non-coding genomic sequences completely identical among human, mouse, and rat species and harbor critical biological functions. We hypothesized that single nucleotide polymorphisms (SNPs) within UCEs are associated with clinical outcomes in colorectal cancer (CRC) patients. Patients and Methods Forty-eight SNPs within UCEs were genotyped in 662 patients with stage I–III CRC. The associations between genotypes and recurrence and survival were analyzed in stage II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Bao et al (2016) for example found association between rs8004379 and prostate cancer-specific mortality. SNPs within UCEs may also be valuable prognostic biomarkers for patients with locally advanced colorectal cancer who receive 5-fluorouracil-based chemotherapy (Lin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bao et al (2016) for example found association between rs8004379 and prostate cancer-specific mortality. SNPs within UCEs may also be valuable prognostic biomarkers for patients with locally advanced colorectal cancer who receive 5-fluorouracil-based chemotherapy (Lin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Different genes and SNPs have been correlated with clinical stage, presence of lymph node metastasis, clinical outcome, increased survival, follow-up after treatment and the risk of recurrence in CRC patients. These markers may be used as a supplement to the tumour lymph nodes metastasis (TNM) staging system, which alone cannot predict cancer prognosis [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, rs10211390 in uc.54 was associated with more advanced CRC stages degrees for patients who had an increased recurrence risk after fluoropyrimidine‐based chemotherapy (5FU). This variation was highlighted as a promising prognostic marker (M. Lin, Eng, Hawk, Huang, Lin, et al, ).…”
Section: Single Nucleotide Variation In T‐ucrsmentioning
confidence: 99%